Adsorption and antimicrobial studies of chemically bonded magnetic graphene oxide-Fe3O4 nanocomposite for water purification. (June 2017) - Raghu, M.S.; Yogesh Kumar, K.; Prashanth, M.K.; Prasanna, B.P.; Vinuth, Raj; Pradeep Kumar, C.B.
Abstract: The present work describes the synthesis of covalent composite of graphene with Fe3 O4, through the formation of amide bond between chloride functionalized graphene oxide (GO) and amine containing Fe3 O4 . The synthesized chemically bonded graphene oxide- Fe3 O4 (GO-Fe3 O4 ) nanocomposite was used as an adsorbent for the removal of malachite green oxalate (MGO) and Eriochrome black T (EBT) in wastewater. The structure, morphology and magnetic properties of prepared nano composite was characterized by X Ray Diffraction (XRD), Fourier transform infrared spectroscopy (FTIR), Transmission Electron Microscope (TEM) and Vibrating Sample Magnetometer (VSM). The effect of the experimental conditions on the adsorption behavior has been investigated by varying the initial concentration, contact time, pH and temperature. The nanocomposite showed a good performance for the adsorption of MGO and EBT from aqueous solution with an adsorption capacity of 179.15 and 160.08 mg g −1 respectively. The Langmuir and Freundlich equations were used to examine the experimental isotherm data. Further it properly fitted with pseudo-second-order kinetic model.The results of this study demonstrate that GO-Fe3 O4 can be used as a potential alternative adsorbent for the proficient removal of dyes from aqueous solution. The GO-Fe3 O4 nanocomposite has been tested against Gram-positive and Gram-negative bacterial strains including Staphylococcus aureus, Bacillus subtilis, Pseudomonas aerugino and Salmonella typhimurium upon which it showed promising antimicrobial activities, thus emphasizing the fact that it can be used for dual purpose in waste water management.